Вплив втрати інформації про орієнтацію потоків вентильного двигуна на базі синхронної машини на його роботу - Морозов, Дмитро Іванович; Шевченко, Іван Степанович; Андреєва, Наталя Іванівна (НТУ "ХПІ", 2017)
Для вентильного двигуна, який представляє собою двигун постійного струму з електронним комутатором, розглянуто формування складових електромагнітного моменту при не співпадінні частоти обертання і частоти напруги живлення якоря. Вентильний двигун такого типу є синхронною машиною оберненої конструкції, тому для аналізу його роботи використані такі ж підходи, як для аналізу роботи традиційної синхронної машини. З використанням векторних діаграм визначені вирази для синхронізуючої та демпферної складових електромагнітного моменту в динаміці.

When changing the load torque of the converter-fed DC motor there is a mismatch of the provisions of the vectors of magnetic fluxes of the stator and armature, and there are additional dynamic electromagnetic moments. For the analysis of the static and dynamic aspects of the machine used vector diagrams as in conventional synchronous machines. Built vector diagram of voltages when the rotor is rotated by the angle of equilibrium and determined expressions for the stress vectors. The expressions for the electromagnetic torque, taking into account the resistance of the field winding. There are synchronizing and damper moments in the dynamic mode. Synchronizing and damper moments are proportional to the square of the sine of the angle of the rotor deflection. At loss of control over the orientation of the magnetic flux in the converter-fed DC motor it goes into a synchronous engine speed rotor vibrations under perturbations.
Impact of loss of information about the orientation of the magnetic flux converter-fed motor based on the synchronous machine at work
Keywords: електромагнітний момент; коливання ротора; якірний струм; синхронізуючий момент; трансформаторний зв'язок; synchronous machine; converter-fed motor; vector diagram; electromagnetic torque; rotor vibrations